Influence of the ligand frameworks on the coordination environment and properties of new phenylmercury(ii) β-oxodithioester complexes. Issue 12 (27th February 2015) - Rajput, Gunjan; Yadav, Manoj Kumar; Drew, Michael G. B.; Singh, Nanhai
Abstract : New luminescent PhHg(ii ) dithioester complexes1–3 have been synthesized and their crystal structures revealed O, S-coordination in1 and2 whereas less preferred S, S-coordination is observed in3 . The keto-form of β-oxodithioester ligands is stabilized in these complexes. Abstract : New phenylmercury(ii ) complexes of the form [PhHg(L1), PhHg(L2) and PhHg(L3)] (L1 = methyl-3-hydroxy-3-( p -methoxyphenyl)-2-propenedithioate (1 ), L2 = methyl-3-hydroxy-3-( p -bromophenyl)-2-propenedithioate (2 ) and L3 = methyl-3-hydroxy-(3-pyridyl)-2-propenedithioate (3 )) have been synthesized and characterized by elemental analysis, IR, UV-Vis, 1 H and 13 C NMR. The crystal structures of1–3 reveal a linear geometry about the mercury atom via ipso -C and S11 atoms.1 and2 exhibited O, S-coordination whereas3 preferred S, S-coordination. Intramolecular Hg⋯O bonding interactions are also observed in1 and2 at distances of 2.638(14), 2.644(10) Å respectively. However in3, incorporation of the 3-pyridyl substituent on the ligand enhanced the proximity of S13 and N14, giving rise to significant intramolecular Hg⋯S and intermolecular Hg⋯N interactions at 3.141(5) Å and 2.77(2) Å respectively generating a 1-D polymeric chain motif. The O, S- or S, S-coordination preference and Hg⋯N interactions have been assessed by DFT calculations. All the complexes show metal perturbed ligand-centred luminescence characteristics in solution and in the solid phase. The band gap values 2.54, 2.66 and 2.61 eV for1, 2 and3, respectively, evaluated from the diffuse reflectance spectroscopy show the semiconducting nature of the complexes.